Characteristics of organisational life cycle stages / Dr Salwa Muda and Musliha Musman - Muda, Salwa; Musman, Musliha (Universiti Teknologi MARA, Negeri Sembilan, 2023)
'Organisations have life cycles just like living organisms do; they go through the normal struggles and difficulties accompanying each stage of the organisational life cycle and are faced with the transitional problems moving to the next phase of development' (Adizes 1989, p. 13). The Organisational Life Cycle (OLC) theory was introduced in the 1920s to explain a life cycle of living organisms that have the phase of life from birth to death. It is later being applied to describe the different stages of firm as a 'non-living' organisation throughout its life cycle (Dalborg 2015). In OLC theory, the change in organisation is known as an accumulation process where the results achieved in later stages are the consequences from the activities in the earlier stages, hence the characteristics acquired by the firms in the earlier stages must be retained in later stages. Competing in an uncertain and turbulent economy requires firms to conduct their operations according to the market challenges, therefore, it is important for firms to address issues and problems in the early stages to avoid unresolved problems emerging in the later stages. The goal of firm establishment is to grow and prosper in many aspects such as financial, management and system, procedures and structure throughout its life supported with strategies that will overcome any issues related to the business. However, the limitations of expert knowledge, information in environmental impacts and allocated resources might hamper the development of the business throughout the life cycles (Bianchi et.al, 2022).